Clinical Safety and Efficacy of Ablation for Atrial Fibrillation Patients With a History of Stroke - Song, Zi-liang; Wu, Shao-hui; Zhang, Dao-liang; Jiang, Wei-feng; Qin, Mu; Liu, Xu (Frontiers in Cardiovascular Medicine, 2021)
Objectives To evaluate the clinical safety and efficacy of radiofrequency catheter ablation for atrial fibrillation patients with a history of stroke. Methods and Results A total of 116 symptomatic, drug-refractory AF patients with a history of stroke, and 1:2 matched patients without a history of stroke were enrolled. Of these, 28 cases occurred stroke within 3 months (Group 1), 88 cases with stroke history longer than 3 months (Group 2), and 232 cases without stroke (Group 3). PVI was performed in all patients, extended to ablation of linear lesions ablation. The periprocedural stroke rates and other procedure-related in-hospital complications did not differ significantly among the 3 groups. The maintenance rate of SR after the procedure showed no significant difference (p = 0.333), 52.7%, 66.4%, and 70.7% in Group 1, 2, and 3, respectively. Furthermore, the comparison between a history of stroke and those without it were also shown no significant difference (p= 0.351). Conclusions Radiofrequency ablation for AF patients occurred stroke, even within 3 months is safe and effective, without higher periprocedural complication rates and recurrence rate.